Kajian Filologi Kitab Al-Mashlahah Fi Al-Tasyri’ Al-Islamiy Wa Najmuddin Al-Thufiy Karya Dr. Mushthofa Zaid - Hamdani, Ahmad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
The main objective of this philological research is to determine the original text (autography), the text that is close to the original (archetypal) or authoritative (authoritative) text, the second is transliterating the text with the main task of maintaining the authenticity / special characteristics of word writing and translating the written text in the original language to the second language, the third is to edit the text as well as possible, the fourth is to describe the position and function of the text under study and clean the text from errors that occur during copying. Based on the description of the purpose of the above research can be formulated some problems namely: the first is in each text there is generally more than one manuscript, which is the original or authoritative manuscript, the second is the text written in characters and languages that are no longer commonly used now that the text is difficult to read and understand the meaning, the third text has not been well presented, no punctuation, paragraph structure and parts of the story so it will be difficult for the reader to understand, the fourth is the position and function of the text is not clear so it is difficult to place this text in the whole of one's thinking or the literature of the region concerned. In this paper will be studied in philological detail on Najmuddin Al-Thufi's text on mashlahah.